The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/nar/gkaa696
|View full text |Cite
|
Sign up to set email alerts
|

YdiV regulates Escherichia coli ferric uptake by manipulating the DNA-binding ability of Fur in a SlyD-dependent manner

Abstract: Iron is essential for all bacteria. In most bacteria, intracellular iron homeostasis is tightly regulated by the ferric uptake regulator Fur. However, how Fur activates the iron-uptake system during iron deficiency is not fully elucidated. In this study, we found that YdiV, the flagella gene inhibitor, is involved in iron homeostasis in Escherichia coli. Iron deficiency triggers overexpression of YdiV. High levels of YdiV then transforms Fur into a novel form which does not bind DNA in a peptidyl-prolyl cis-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 89 publications
6
29
0
Order By: Relevance
“…Using both the classic Pb(Ac) 2 detection test and a fluorescent-based probe WSP5 (Zhang et al, 2020), we confirmed that, the production of H 2 S in cbl deletion strain was significantly lower than that of WT in M9 medium (Figs. 3A and 3B).…”
Section: Cbl Affects the Generation Of H 2 Ssupporting
confidence: 56%
See 1 more Smart Citation
“…Using both the classic Pb(Ac) 2 detection test and a fluorescent-based probe WSP5 (Zhang et al, 2020), we confirmed that, the production of H 2 S in cbl deletion strain was significantly lower than that of WT in M9 medium (Figs. 3A and 3B).…”
Section: Cbl Affects the Generation Of H 2 Ssupporting
confidence: 56%
“…For the EMSA, DNA probe was incubated with Cbl protein samples in reaction buffer (10 mM Tris–HCl, one mM MgCl 2 , one mM DTT, 40 mM KCl, 0.1 mg/mL BSA, 5% (w/v) glycerol) at 37 °C for 30 min. After the samples were separated using a 6% native acrylamide gel ( Zhang et al, 2020 ), the gel was then exposed to a phosphorscreen and visualized on Typhoon FLA 9500.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was heated at 95°C for 10 min and slowly cooled to room temperature. About 15 μg of extracted protein in binding buffer (pH 7.5, 10 mM TrisHCl, 1 mM MgCl 2 , 40 mM KCl, 0.1 mg/ml BSA, 5% glycerol) was incubated with 200 fmol of FAM-labeled probes at room temperature for 15 min [ 62 , 63 ]. An antibody for His (1.5 μg) was added to the binding reaction in the supershift experiment.…”
Section: Methodsmentioning
confidence: 99%
“…These large-amplitude and long time scale motions are certainly characteristic of multidomain transcriptional regulators [126,127]. In many cases, they are coupled or obscured by changes in the oligomerization state of the protein that is derived from intermolecular interactions between the sensory domains or even the DNA-binding domains [128][129][130]. Overall, when extensive conformational changes occur upon inducer binding, it is still a challenge to obtain direct experimental information about dynamic changes.…”
Section: Ensemble Models Of Allosterymentioning
confidence: 99%